2012
DOI: 10.1016/j.midw.2011.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Screening for alcohol and drug use in pregnancy

Abstract: data were collected from two sources. First, 32 women who reported use of alcohol or other drugs during pregnancy at initial screening were then asked to complete a full substance use survey. Second, data were collected from charts of 349 new clients who attended the antenatal clinic during the study period. Both sensitivity (86%, 67%) and positive predictive value (100%, 92%) for alcohol and other drug use respectively, were high. Only 15% of surveyed women were uncomfortable about being screened for substanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 15 publications
0
25
0
1
Order By: Relevance
“…In addition and consistent with other research with health professionals in WA [84], some midwives expressed attitudes that may act as barriers to addressing alcohol consumption during pregnancy. These were that asking every pregnant woman about whether they have consumed alcohol during pregnancy could cause anxiety and guilt, uncover problems that are difficult for midwives to address, and lead to women feeling judged, even though Australian women surveyed in an antenatal clinic reported they do not feel judged by midwives [81]. Strategies to address such attitudes including how to manage difficult conversations and emotional responses should be incorporated in professional development for midwives [89].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition and consistent with other research with health professionals in WA [84], some midwives expressed attitudes that may act as barriers to addressing alcohol consumption during pregnancy. These were that asking every pregnant woman about whether they have consumed alcohol during pregnancy could cause anxiety and guilt, uncover problems that are difficult for midwives to address, and lead to women feeling judged, even though Australian women surveyed in an antenatal clinic reported they do not feel judged by midwives [81]. Strategies to address such attitudes including how to manage difficult conversations and emotional responses should be incorporated in professional development for midwives [89].…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire was based on the review of the literature and adapted from previous surveys conducted with health professionals in WA [67,7376], and other surveys of health professionals [60,61,68,77–81]. During the questionnaire development we consulted with a WACHS Midwifery Advisor, the Steering Group, and the Midwifery Reference Group.…”
Section: Methodsmentioning
confidence: 99%
“…Verbal screening for self-reported use was noted to be acceptable to patients in one study. 13 Women who report use should then be encouraged to stop and referred to local substance use disorder programs if needed.…”
Section: Screening and Testing For Marijuana Usementioning
confidence: 99%
“…152,153 In both Australia and the Netherlands, while women found screening acceptable, midwives were reluctant to discuss alcohol with women in their care and felt that they needed additional training in asking difficult questions and in managing those who disclosed that they were continuing to drink alcohol while pregnant. 154,155 A small-scale qualitative study of the factors that influence women's disclosure of substance use in pregnancy in Australia found that a non-judgemental rather than confrontational approach encouraged disclosure. Midwives reported a good rapport and that trusting relationships were essential; for women, direct questions, continuity of care and addressing child protection issues early and honestly all helped.…”
Section: Assessment and Detection Of Problem Drinking In Pregnancymentioning
confidence: 99%